Gelatin methacrylate hydrogel microparticle-based 3D platform for elasticity-driven multi-lineage differentation of human mesenchymal stem cells - Pappalardo, Francesco (2022)
Understanding the mechanisms of the fate of stem cells is one of the major cornerstones of regenerative medicine research. Mesenchymal stem cells (MSCs) are multipotent cells that can differentiate into muscle, cartilage, bone, fat and nerve cells, and the complex mechanisms that they undergo are still not fully understood. Advances in cell signalling and developmental biology provided rudimentary pathways to differentiate MSCs in 2D culture to the aforementioned cell types, but the cellular microenvironment contains not just chemical signals but also those that are mechanical in nature. Previous research showed that matrix stiffness plays a significant role in MSC differentiation and that substrates can be tuned in their mechanical properties to tailor MSC lineage determination. However, most of the research performed in this area are in a 2D format, where it does not capture the 3D interaction effects of cells in culture and other physical aspects of the biomaterials such as curvature. Transitioning into a 3D platform can enable us to determine more accurately the physiological nature of stem cell behaviour.